PENGARUH KEPEMIMPINAN, MOTIVASI DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI PADA DINAS PERIKANAN KABUPATEN BARRU - M Natsir Mallawi (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2022)
This study aims to examine and partially analyze the effect of leadership, motivation and work discipline on the performance of the Barru District Fisheries Service Employees. To test and analyze the joint influence of leadership, motivation and work discipline on the performance of the Fisheries Service Office of Barru Regency. This study used two approaches, namely descriptive and explanatory approaches. Data collection methods used are questionnaires and document studies. The analytical method used is descriptive statistical analysis and multiple linear regression analysis. The results of the study show that: 1) Partially indicate that the leadership variable has a dominant effect on employee performance, this indicates that the higher the leadership, the higher the employee performance at the Fisheries Service Office of Barru Regency. 2) Partially shows that the motivation variable has an effect on employee performance, this shows that the better the motivation that is followed will further improve the performance of the employees at the Fisheries Service of Barru Regency. 3) Partially shows that the work discipline variable has an effect on employee performance, this shows that the better work discipline, the better the performance of employees at the Fisheries Service of Barru Regency. And 4) Simultaneously shows that the variables of Leadership, Motivation and Work Discipline have an effect on employee performance, which means that an increase in Leadership, Motivation and Work Discipline will affect the increase in employee performance at the Fisheries Service Office of Barru Regency by 84.4%